Imaging of Ampullary and Periampullary Conditions - Sunnapwar, Abhijit; Nagar, Arpit; Katre, Rashmi; Khanna, Lokesh; Sayana, Hari Prasad (Journal of Gastrointestinal and Abdominal Radiology, 2021)
The ampulla of Vater is formed by the union of the pancreatic duct and the common bile duct and is also known as hepatopancreatic ampulla or hepatopancreatic duct. The ampulla is surrounded by a muscular valve known as the sphincter of Oddi, which controls the flow of bile and pancreatic juices into the duodenum in response to food. The ampulla is also an important embryological landmark as it marks the anatomical transition from foregut to the midgut. Because of this, it is a watershed zone where the blood supply changes from the celiac axis to the superior mesenteric artery. Radiologic evaluation of the ampulla and the periampullary region is challenging because it requires an understanding of the embryology, the normal appearance, and different anatomic variants. Also, a wide variety of pathologies can occur in this region. The purpose of this review is to present the normal anatomy of the ampulla and the periampullary region on different imaging modalities and to summarize the imaging features of the common variants, and benign and malignant ampullary and periampullary conditions. Understanding of the normal anatomical appearance and variants along with the knowledge of common pathologic conditions affecting the ampulla and periampullary conditions can help radiologists in making accurate diagnosis resulting in optimum patient care.
Keywords: ampullary; biliopancreatic junction; neoplasms; periampullary